Preserving Public Broadcasting Archives in the Digital Era: Circulatory Stories and Technologies, the Digital Turn, and the Return of the Past in West Africa - (:unkn) unknown (My University, 2020)
Broadcasting archives have been being digitized in West Africa since the 2000s. Their digital transfer, presented as both a solution to their decay and a necessary step to take them into the new century, presents considerable challenges. This article, while emphasizing the historiographical value of the archives as sources and traces, argues that the processes they undergo, which also participate in these technical objects’ afterlife, are connected to a long and circulatory history of cooperation in broadcasting. Located at the interface of past, present, and future, they also provide an opportunity to question certain geopolitical fracture lines, especially those of knowledge and memory.
Keywords: African Research